Compliance with focused antenatal care services: do health workers in rural Burkina Faso, Uganda and Tanzania perform all ANC procedures? - Conrad, Paul; Neuhann, Florian; Müller, Olaf; Sarker, Malabika (Tropical medicine & international health, 2012)
Objective To assess health workers’ compliance with the procedures set in the focused antenatal care (ANC) guidelines in rural Uganda, Tanzania and Burkina Faso; to compare the compliance within and among the three study sites; and to appraise the logistic and supply of the respective health facilities (HF). Methods The cross-sectional study was conducted in the rural HF in three African countries. This descriptive observational study took place in HF in Nouna, Burkina Faso (5), Iganga, Uganda (6) and Rufiji, Tanzania (7). In total, 788 ANC sessions and service provisions were observed, the duration of each ANC service provision was calculated, and the infrastructures of the respective HF were assessed. Results Health workers in all HF performed most of the procedures but also omitted certain practices stipulated in the focused ANC guidelines. There was a substantial variation in provision of ANC services among HF within and among the country sites. The findings also revealed that the duration of first visits was <15 min and health workers spent even less time in subsequent visits in all three sites. Reagents for laboratory tests and drugs as outlined in the focus ANC guidelines were often out of stock in most facilities. Conclusion Health workers in all three country sites failed to perform all procedures stipulated in the focused ANC guideline; this could not be always explained by the lack of supplies. It is crucial to point out the necessity of the core procedures of ANC repeatedly.
Gesehen am 05.10.2018
First published: 08 December 2011